2012
DOI: 10.6063/motricidade.8(4).1555
|View full text |Cite
|
Sign up to set email alerts
|

Alongamento passivo agudo não afeta a atividade muscular máxima dos ísquiotibiais

Abstract: RESUMO O alongamento agudo pode influenciar a produção de força em diferentes tarefas e performances esportivas. O objetivo do presente estudo foi investigar a influência do alongamento passivo agudo na atividade elétrica do músculo bíceps femoral (BF) e na força dos músculos isquiotibiais (IT). Participaram 14 adultos jovens, sedentários fizeram parte deste estudo. Foram requisitados aos sujeitos que realizassem contrações isométricas máximas antes e após um protocolo de alongamento passivo. O protocolo de al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…There is a study involving 14 sedentary young adults that collected the electromyographic signal (EMG) of the biceps femoris muscle before and after passive hamstring stretching with 3 sets of 60 seconds. As a result, the acute effects of passive stretching did not significantly influence the muscle activation pattern of the femoral biceps (2) . They explain that the divergent findings may be related to several factors such as the characteristics of the evaluated samples, gender, age, intensity and duration of stretching (4) .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There is a study involving 14 sedentary young adults that collected the electromyographic signal (EMG) of the biceps femoris muscle before and after passive hamstring stretching with 3 sets of 60 seconds. As a result, the acute effects of passive stretching did not significantly influence the muscle activation pattern of the femoral biceps (2) . They explain that the divergent findings may be related to several factors such as the characteristics of the evaluated samples, gender, age, intensity and duration of stretching (4) .…”
Section: Discussionmentioning
confidence: 82%
“…Pre-exercise static stretching is believed to reduce the risk of injury and improve performance. However, recent studies have reported that pre-exercise stretching may decrease strength production and muscle activation or have not shown a significant effect on muscle activation (2,3) . Such divergences about the potential harms or benefits that stretching techniques can generate on muscle performance prompt the study of therapeutic approaches that can support the use of stretching as an effective intervention plan in clinics, gyms or sports training centers (4,5) .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The benefits of warming-up are the increase in muscle temperature and energy metabolism, as well as increased tissue elasticity improving the function of the central nervous system and the recruitment of neuromuscular motor units (10,11) , that generate gains in muscle strength, hypertrophy of the musculoskeletal system, improvement in sports performance and gains in physical conditioning (6) . Bley, Nardi and Marchetti (12) , claim that stretching before exercise decreases isometric or dynamic strength, electromyographic activity and peak concentric torque. According to Nogueira et al (13) , stretching aims to increase mobility and expandability of soft tissues, making range of motion more effective, as well as helping to reduce spasm.…”
Section: Introductionmentioning
confidence: 99%